Program Pemberian Tablet Fe di Sekolah dan Penurunan Kejadian Anemia pada Remaja Putri di Kota Padang: Program for Providing Iron Tablets in Schools and Reducing the Incidence of Anemia among Adolescent Girls in Padang City - Asriyanti, Rita; Azrimaidaliza, Azrimaidaliza; Elda, Frima; Dwinatrana, Khiky (Universitas Airlangga, 2024)
Background: Anemia among reproductive-age women can lead to significant nutritional issues for future generations. In Indonesia, the anemia prevalence rate among women is alarmingly high at 30.44%. A key strategy to reduce anemia is the distribution of iron tablets (Fe) in schools. Objectives: This study aimed to analyze the effectiveness of the iron tablet program in schools and its relationship to the incidence of anemia among adolescent girls in Padang City. Methods: A mixed-methods approach was utilized, combining quantitative and qualitative techniques. A cross-sectional design assessed the relationship between iron tablet distribution and anemia prevalence. Qualitative data were gathered through in-depth interviews to explore the program's implementation. The study involved two schools in Padang City, randomly selecting a sample of 274 adolescent girls. Data were collected using standardized instruments, analyzed with statistical software, and examined using multiple logistic regression tests. Results: The iron tablets program hasn’t been optimally implemented. The study found 28.1% of adolescent girls were anemic. An iron tablet consumption history (p-value=0.035), the quantity consumed (p-value=0.034), father's education level (p-value=0.039), and nutritional knowledge (p-value=0.032) related with anemic. Girls who did not consume iron tablets were 3.03 times more likely to be anemic. Many expressed concerns about the potential negative effects of iron tablets. Conclusions: This study reveals a troubling prevalence of anemia among adolescent girls, with nearly one-third affected. Inadequate iron tablet consumption, along with parental education and nutritional knowledge, significantly contributes to this issue. Concerns about side effects emphasize the urgent need for targeted educational interventions.